The effect of early orthodontic treatment on long-term stability of Class II malocclusions - Mohammad K Alam; Rana Elbeshbeishy; Huda M Abutayyem; Raghad Fayez H Albalawi (Wolters Kluwer Medknow Publications, 2024)
Background: Class II malocclusions are a common dental issue characterized by the misalignment of the upper and lower teeth. Early orthodontic treatment is often considered to correct these malocclusions, but its long-term effectiveness remains unclear. Materials and Methods: In this study, we examined the impact of early orthodontic treatment on the long-term stability of Class II malocclusions. We conducted a retrospective analysis of dental records from a sample of 150 patients who had received early orthodontic treatment for Class II malocclusions. The treatment involved braces and other orthodontic appliances. We compared their dental measurements before and after treatment, with a follow-up period of 5 years. Results: Our analysis revealed that the early orthodontic treatment led to a significant improvement in the alignment of upper and lower teeth, as indicated by a reduction in the overjet (the horizontal distance between upper and lower incisors). The mean overjet reduction was 3.2 millimeters. Furthermore, the Angle's Class II molar relationship was corrected in 80% of the cases. Conclusion: Early orthodontic treatment for Class II malocclusions demonstrated positive long-term stability, as evidenced by a reduction in overjet and improvement in molar relationships.